Towards Cultural Materialism: Criticism and Hegemony in Raymond Williams - Valle Alcalá, Roberto Del (Estudios Ingleses de la Universidad Complutense, 2010)
This article analyses Raymond Williams’ concept of “cultural materialism” through the theoretical and political contexts which framed his thought in the 1970s. His dialogue with the continental Marxist tradition – Lucien Goldmann, Georg Lukàcs and Antonio Gramsci, principally – marks a significant shift from the organicist and broadly reformist ideas articulated in earlier works such as Culture and Society (1958) and The Long Revolution (1961). Williams’ development of the Gramscian theory of hegemony in particular offers both a fresh start for critical practice beyond the narrow disciplinary margins of “the literary”, and a sharp tool of analysis for new social antagonisms and problem-spaces.
Keywords: Culture; Materialism; Marxism; Hegemony